Not in My Back Yard: Public Perceptions and Terrorism. (March 2019) - Avdan, Nazli; Webb, Clayton
Why does the public care more about some terrorist attacks than others? In recent years, there has been a wave of terrorist attacks carried out by similar terrorist organizations, but these attacks have produced disparate public responses. Existing research shows that terrorist attacks are more traumatic for people who live near terrorist targets, but this research cannot explain differences in public attitudes about attacks occurring in other countries. We argue that threat perceptions are shaped by the physical and personal proximity of terrorist attacks. The identities of the victims are rarely known. People impute the characteristics of victims based on the country where the attack occurred. These perceived identities determine the empathy people feel toward victims and affect perceptions of terrorist threats. People feel a greater sense of vulnerability when attacks occur near their borders. We test these arguments using a series of online experiments. We find that the location of the attack and the race and nationality of the victims drive threat perceptions.